2006
DOI: 10.1007/s10934-006-7004-y
|View full text |Cite
|
Sign up to set email alerts
|

Acetalization of ketones on K-10 clay and rare earth exchanged HFAU-Y zeolites: A mild and facile procedure for the synthesis of dimethylacetals

Abstract: Dimethylacetals of ketones; cyclohexanone, acetophenone, and benzophenone have been prepared by reacting ketones with methanol under mild reaction conditions. Large pore zeolites (H-Y and its rare earth metal, Ce 3+ , La 3+ , and RE 3+ modified forms), and mesoporous clay (K-10 montmorillonite and its cerium exchanged counterpart) with regular pore structure, silica and silica-alumina have been used as catalysts. Clay catalysts are found to be much more active than zeolites, thanks to slightly bigger pore size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Acetalization of aldehydes can be performed in the presence of weak acids, while ketones generally need stronger ones such as sulfuric, hydrochloric, or p-toluenesulfonic acid. Acid zeolites and mesoporous aluminosilicates have been used as catalysts for the synthesis of dimethylacetals of different aldehydes and ketones using trimethylorthoformate or methanol as reactants, giving in general good yields [82][83][84][85][86][87][88].…”
Section: Acetalization Of Carbonyl Compoundsmentioning
confidence: 99%
“…Acetalization of aldehydes can be performed in the presence of weak acids, while ketones generally need stronger ones such as sulfuric, hydrochloric, or p-toluenesulfonic acid. Acid zeolites and mesoporous aluminosilicates have been used as catalysts for the synthesis of dimethylacetals of different aldehydes and ketones using trimethylorthoformate or methanol as reactants, giving in general good yields [82][83][84][85][86][87][88].…”
Section: Acetalization Of Carbonyl Compoundsmentioning
confidence: 99%
“…27 Furthermore, mesoporous aluminosilicate can effectively catalyze the reaction between carbonyl compounds and methanol. 28,29 The discovery of natural materials with high catalytic performance represents an alternative to pollutant and corrosive homogeneous catalysts. 30−33 Natural aluminosilicates such as zeolites and more particularly clays are economical, recyclable, nontoxic, noncorrosive, easy to handle, and effective catalysts in several chemical transformations.…”
Section: Introductionmentioning
confidence: 99%
“…As a solid acid catalyst, montmorillonite clay has a great potential to catalyze dehydration reactions [18][19][20]. Several studies revealed that the activity of montmorillonite clay in specific reactions such as acetalization and esterification is higher compared to zeolites in general, mainly because of the presence of mesopores in the montmorillonite clay structure [21][22][23]. Another catalytic dimension is added to clays, when used as support for redox-active metals in various reactions [6,24].…”
Section: Introductionmentioning
confidence: 99%